Assembly and antigen-presenting function of MHC class I molecules in cells lacking the ER chaperone calreticulin. - Gao, B; Adhikari, R; Howarth, M; Nakamura, K; Gold, M; Hill, AB; Knee, R; Michalak, M; Elliott, T (2002)
MHC class I molecules expressed in a calreticulin-deficient cell line (K42) assembled with beta 2-microglobulin (beta2-m) normally, but their subsequent loading with optimal peptides was defective. Suboptimally loaded class I molecules were released into the secretory pathway. This occurred despite the ability of newly synthesized class I to interact with the transporter associated with antigen processing (TAP) loading complex. The efficiency of peptide loading was reduced by 50%-80%, and impaired T cell recognition was observed for three out of four antigens tested. The peptide-loading function was specific to calreticulin, since the defect in K42 could be rectified by transfection with calreticulin but not a soluble form of calnexin, which shares its lectin-like activity.